A quantitative investigation of hemodynamic adaptation to pregnancy using uterine artery Doppler ultrasonography and finger photoplethysmography. (November 2014) - Han, Nan; Luo, Xiaomin; Su, Fangming
<x xml:space="preserve">Abstract</x> Objective: Normal pregnancy is characterized by maternal hemodynamic adaptations of cardiovascular system and uterine artery. We aimed to investigate quantitatively the relationship between uterine artery Doppler (Ut AD) ultrasonography and finger photoplethysmography (PPG) in each of the three trimesters. Methods: Eighty normal pregnancy subjects were recruited from the nulliparous women with uncomplicated singleton pregnancy presenting for a routine ultrasound scan and divided into three groups according to their trimester. Comparative analysis were conducted between Ut AD ultrasonography and finger PPG within and across trimesters, particularly with focus on the relationship between Uterine Artery Resistance Index (UtA RI) and photoplethysmographic reflection index (PPG RI) throughout pregnancy. Additional 10 preeclampsia patients in third trimester were enrolled for comparison. Results: Both UtA RI and PPG RI were markedly decreased with gestation in normal pregnancy and generally consistent with each other in trend. The preeclampsia patients of third trimester were significantly higher in both indices, even more than normal pregnancy subjects of first trimester. Conclusions: The results of this study revealed clear relationship between UtA RI and PPG RI throughout pregnancy which could be exploited to enhance the potential ability in early recognition of pathophysiologic process in maternal adaptation and prediction of complicated pregnancy.